Productivity and profitability of lowland rainfed rice (Oryza sativa) - based cropping sequences in Andaman - RAJ, M MICHAEL; PREMANIK, S C; SAGAR, R L (The Indian Journal of Agricultural Sciences, 2013)
An experiment was conducted for 3 years during 1993-96 on the productivity and profitability of rice and rice-based cereal, maize(Zea mays L.); pulses, greengram (Phaseolus radiatus L.) and blackgram (Phaseolus mungo L.); oilseeds, sesame(Sesamum indicum L.); and vegetables, cowpea (Vigna unguiculata (L.) Walp) and okra(Hibiscus esculentus L.) sequences inthe farmers' field in Andaman Islands. The results revealed that the rice-vegetable cropping sequences gavehigher yield equivalent than others. The production efficiencies of rice-vegetable cropping sequences were higher (31.146.9kg/ha/day) compared to rice-cereals and rice-pulses. The land-use efficiency of these sequences were also higher tothe maximum extent of 97.3%. However, the energy input-output ratio was higher with sesame (1.79 and 1.8) in 2 and3 crop sequences than others. The net retums and benefit: cost ratio of the rice-vegetable (cowpea and okra) sequencesRs 17 145-25 825 and 1.65-1.86 respectively) were significantly higher than all other sequences. Employment potential wasalso higher with these crop sequences. However, double crop of rice increased significantly the rice equivalent yield, net returns and efficiencies of the crop sequences over single crop of rice. Therefore, rice-rice-vegetables like okra/cowpea proved highly productive and remunerative cropping sequences in these islands.